Synthesis, anion binding studies and applications of mono- and bimetallic lanthanide complexes - Mason, L (2017)
This work describes the preparation and study of lanthanide complexes derived from heptadentate DO3A and DO3AM ligands. The work described encompasses a range of synthetic studies using conventional Click chemistry, novel gold catalysed couplings to prepare mono- and bi- metallic complexes and synthesis of DO3AM derivatives. These complexes have been used in a variety of studies to explore proton and anion binding events, and to develop catalysts for fluorination in protic solvents. Chapter one describes the fundamental properties of the lanthanides with a focus on their luminescent behaviour, as well as a brief review of possible applications for lanthanide ions and complexes. Chapter two explores the use of click reactions, firstly with propargylDO3A and 2- azidopyridne to explore any pH dependant behaviour of the complexes. The corresponding d-f hybrids of these complexes were also explored to investigate how the addition of a d block metal can affect the behaviour of d-f hybrids compared to the parent complex. This chapter also explores the novel synthesis of a strained dibenzocyclooctyne lanthanide complex, that has potential for efficient formation of bioconjugates using in vivo bio-orthogonal click reactions. Chapter three describes the development of a novel synthetic method that uses lanthanide complexes in novel three component gold catalysed couplings to form new lanthanide architectures, and study their binding affinity for anions. We also describe how this methodology can be extended to form bimetallic lanthanide complexes. These bimetallic systems form ternary complexes with aryl dicarboxylates, in which guest binding can be used to modulate the intramolecular energy transfer mechanisms giving rise to a ratiometric red/green response. Chapter four defines the synthesis of rigid, chiral heptadentate DO3AM derivatives bearing aspartate derived pendant arms, and explores their fluoride binding by NMR and luminescence, revealing that binding of axial fluoride is less favourable than fluoride binding in the plane of the carbonyl donors. The use of these complexes as catalysts is also investigated for the fluorination of α-halocarboxylic acids. Chapter five summarises the work done throughout the thesis, highlighting some overarching conclusions, as well as describing areas for further study. Chapter six provides experimental procedures and characterisation data for the compounds studied.